2021
DOI: 10.1039/d0cp05606e
|View full text |Cite
|
Sign up to set email alerts
|

Metastability of palladium carbide nanoparticles during hydrogen release from liquid organic hydrogen carriers

Abstract: The metastability of the Pd6C phase results from the thermodynamically favorable growth of graphene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…A crucial aspect in LOHC development is selection of the proper catalytic system for the hydrogenation and dehydrogenation reactions. Various catalysts have been used for both the hydrogenation and dehydrogenation reactions, including precious metals platinum (Pt) [3], palladium (Pd) [4] and ruthenium (Ru) [5], supported on alumina (Al 2 O 3 ), carbide (C) and silica (SiO 2 ), to achieve chemical routes with high selectivity under sufficiently mild reaction conditions [6]. To understand the performance of Ru-based catalysts, the hexagonal close-packed (hcp) phase of Ru, the dominant phase in bulk Ru, has been studied extensively, both experimentally and theoretically using first-principles methods [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A crucial aspect in LOHC development is selection of the proper catalytic system for the hydrogenation and dehydrogenation reactions. Various catalysts have been used for both the hydrogenation and dehydrogenation reactions, including precious metals platinum (Pt) [3], palladium (Pd) [4] and ruthenium (Ru) [5], supported on alumina (Al 2 O 3 ), carbide (C) and silica (SiO 2 ), to achieve chemical routes with high selectivity under sufficiently mild reaction conditions [6]. To understand the performance of Ru-based catalysts, the hexagonal close-packed (hcp) phase of Ru, the dominant phase in bulk Ru, has been studied extensively, both experimentally and theoretically using first-principles methods [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, optimization studies for LOHC-based hydrogen storage and transportation systems are actively conducted worldwide, and demonstration projects are underway to integrate LOHC systems with existing hydrogen infrastructure. However, continuous research and development efforts are needed due to the relatively low hydrogen density and availability compared to other hydrogen storage compounds (such as methanol and ammonia) [124,[128][129][130][131][132][133][134][135]. Various LOHCs based on substances including benzene and toluene have been researched, and their characteristics are summarized in Table 5 [126].…”
Section: Liquid Organic Hydrogen Carriermentioning
confidence: 99%
“…Seriani et al 21 have reported the formation of a metastable carbide that corresponds to 13–14% of C concentration in which hydrogen diffusion is hindered as compared to pristine Pd. This Pd 6 C metastable carbide formation has been further investigated through experimental 22 and theoretical methods. 23 In the recent study of He et al , C diffusion into the Pd(100) and Pd(111) surface models show zigzag trajectories for the migration pathways and a non-uniform distribution in the slab.…”
Section: Introductionmentioning
confidence: 99%